Pengaruh Kompensasi dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT Cendana Han Wijaya - Tan, Riny; Heryenzus, Heryenzus (LPPM Universitas Putera Batam, 2021)
The success of a company is influenced by employee performance. Every company will strive to improve the performance of its employees so that company goals can be achieved. One of the factors that can affect a person's performance is compensation and motivation. Performance appraisal is needed to determine the results or level of success of an employee. The purpose of this research is to determine the extent to which compensation and motivation significantly influence employee performance at PT Cendana Han Wijaya. The results of the T test prove partially, the results of the research state that compensation and motivation have a significant effect on employee performance at PT Cendana Han Wiajay and the coefficient of determination (R2) obtained is 52.9% of employee performance is influenced by compensation and motivation variables. While the remaining 47.1% is influenced by other variables.